INTERNAL OR EXTERNAL STANDARD TECHNIQUES FOR QUANTIFICATION OF FREE FATTY ACIDS (FFAs) IN RAW MILK AND KEFIR SAMPLES - AHMET DURSUN; ZEHRA GÜLER (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
Free fatty acids (FFAs) can be analyzed by chromatographic methods as both qualitatively and quantitatively. The concentration of FFAs can be estimated by using internal or external standard techniques. The object of this study was to determine the recovery and repeatability of individual FFA (C2-C18:1) in milk and kefir, using internal or external standard (calibration curve). The FFAs adsorbed on aluminum oxide from samples are desorbed in isopropyl alcohol containing formic acid, which are analyzed using a gas chromatography-mass spectrometry (GC-MS) coupled with capillary column. The RSD of FFAs ranged from 2.77 % to 5.82 % for milk and from 1.02 % to 6.82 % for kefir. The recoveries of FFAs ranged from 82 % to 109.9 % and from 83.6 % to 109.3 %, respectively. The lowest recovery was obtained for hexadecanoic acid (82 %) in milk by the calculation relative to internal standard using relative correction factor. No significant differences in the concentrations of individual FFA were observed between internal and external standard techniques for milk but hexadecanoic and octadecenoic acids in kefir were higher at calculation by external standard compared to internal. In conclusion, the individual FFA showed a good repeatability in both kefir and milk. The high ethanol and acidity contents of kefir samples did not show a blocking effect on the alumina sorbent for isolation or releasing of FFAs.